2011
DOI: 10.1353/lib.2011.0008
|View full text |Cite
|
Sign up to set email alerts
|

"Prison Libraries" in Japan: The Current Situation of Access to Books and Reading in Correctional Institutions

Abstract: This article discusses the present state of access to books and other reading materials for inmates in Japan's correctional facilities. While no professionally managed libraries are provided at these facilitieswhich explains why the term Prison Libraries in the title of this article is placed in quotation marks-incarcerated persons have the opportunity to obtain personal books, magazines, and newspapers through purchase or gifts. The prison administration also provides a certain number of reading materials at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Finally, Nakane (2011) indicates in his article that although in Japan's correctional facilities a certain number of reading materials are available at various locations within the institutions, no functional library space is provided, and the materials are dispersed throughout the facility, including work areas (factories), living quarters and so-called 'library work areas'. In addition, he points out that Japanese prisons do not employ professional librarians; rather, the prison staff and inmates who operate and supervise the 'library' sporadically acquire materials and provide access to them (Nakane, 2011: 446-447, 449, 451).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Nakane (2011) indicates in his article that although in Japan's correctional facilities a certain number of reading materials are available at various locations within the institutions, no functional library space is provided, and the materials are dispersed throughout the facility, including work areas (factories), living quarters and so-called 'library work areas'. In addition, he points out that Japanese prisons do not employ professional librarians; rather, the prison staff and inmates who operate and supervise the 'library' sporadically acquire materials and provide access to them (Nakane, 2011: 446-447, 449, 451).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in practice, library ethics and philosophies are inherently in conflict with the missions and security policies of correctional institutions, and prison librarians worldwide are required to restrict the acquisition of, and access to, so-called 'sensitive' literature. Several authors also noted that, in their countries, there is a lack of popular types of reading materials (newspapers and magazines) which enable prisoners to keep abreast of what is happening in the world outside the prison walls (Nakane, 2011;Zybert, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current study identified the trend that in Pakistan, much of the library collection in the prison libraries such as India, Nigeria, Croatia, Indonesia and Japan is mainly developed through gifted material from the concerned individual, religious groups and NGOs. (Albert, 1989; Eze, 2016; Emasealu and Popoola, 2016; Mahale, 2016; Nakane, 2011; Omagbemi and Odunewu, 2007; Rahmi and Patrick, 2015; Šimunić et al , 2016; Singh, 2014). In this regard, the Pakistani prison department does not allocate any budget to the libraries to meet the prisoners’ information needs.…”
Section: Discussionmentioning
confidence: 99%
“…However, one significant practice was, some of these libraries were connected with public libraries, such as Edinburgh prison library won UK change lives award, the library was designed and built by prisoners (Maculan et al , 2014). According to Kenichi Nakane (2011) Japanese prisons do not have a functional library space; also, there is no concept of inter library loan in prison and public libraries. Ludmila, Popow and Mayrink da Costa (2003) reveals that the prison systems in the state of Rio de Janeiro have no library.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Prison libraries in Brazil have small collections of books and cannot be considered libraries (Da Costa, 2003). He also revealed that the correctional institution in the state of Rio de Janeiro (Brazil) had no library in Japan, most of the prison library material is acquired by inmates or through gifts (Nakane and Noguchi, 2011). In Uganda, prison libraries have inadequate African literature.…”
Section: Major Issues and Challenges For Prison Libraries Around The ...mentioning
confidence: 99%